A Niche Modelling Approach Adapted to Small Datasets With Permian/Triassic Conodonts as a Case Study - Pauline Guenser; Alexandre Pohl; Mathéo Leroy; Dominik Hülse; Grégory Beaugrand (Journal of Biogeography, 2026)
Aim The emergence of Ecological Niche Modelling (ENM) in the 2000s advanced our ability to evaluate how biotic and abiotic factors constrain species distribution. Although highly employed in ecological investigations, the application of ENM in palaeontology (‘palaeoENM’) is less common, and the scarcity of the fossil record makes predictions uncertain with current ENM routines. Here we propose a methodological assembly especially designed for small datasets to enhance palaeoENM studies. Location Global. Time Period Permian/Triassic boundary (ca. 252 Ma). Major Taxa Studies Two conodont (Vertebrata, Conodonta † ) genera, Clarkina and Hindeodus . Methods We use the Non‐Parametric Probabilistic Ecological Niche (NPPEN) model improved with the generation of pseudo‐presences (PPs) to complete the dataset before applying the ENM, called NPPEN‐PP hereafter (i.e., NPPEN with PPs). NPPEN‐PP is performed using environmental parameters simulated with an Earth System Model constrained by proxy data. Then, we use Shapley values to investigate the individual contribution of each environmental variable in space and time in the model. Finally, we propose a simple procedure to quantify and compare the robustness of the simulations among studied taxa. Results The generation of PPs increases the performance of NPPEN but their robustness differs between the two taxa, probably due to a difference in sampling effort. The resulting palaeoENMs indicate that the two conodont taxa occupied distinct, albeit partially overlapping, ecological niches and that their distributions were influenced by different environmental variables. In particular, Hindeodus species remained in low latitudes and expanded their distribution to high latitude while Clarkina species moved from low to high latitude during the mass extinction event. The Shapley values allow us to explain this discrepancy by a higher adaptability of Hindeodus to anoxic environments compared to Clarkina . Main Conclusions We assess for the first time, through modelling, the ecological differentiation of two conodont genera. The methodological assembly proposed here can help palaeontologists but also ecologists to perform reliable ENM on small datasets and so extend our knowledge on drivers of past and present taxa distribution.

Paleozoic and Mesozoic oceanic anoxic events and biotic crises - Haijun Song; Alexandre Pohl; Alexander M. Dunhill; Xi Chen (Global and Planetary Change, 2026)

Spatial biases in oxygen-based Phanerozoic seawater temperature reconstructions - Alexandre POHL; Thomas W. WONG HEARING; Arnaud BRAYARD; Ethan GROSSMAN; Michael M. JOACHIMSKI; Guillaume LE HIR; Thomas LETULLE; Daniel J. LUNT; Mathieu MARTINEZ; Emmanuelle PUCEAT; Guillaume SUAN; Paul VALDES; et al. (Earth and Planetary Science Letters, 2025)

Calcium isotopes support spatial redox gradients on the Tethys European margin across the Triassic-Jurassic boundary - Ashley N. Prow-Fleischer; Zunli Lu; Clara L. Blättler; Tianchen He; Pulkit Singh; Preston Cosslett Kemeny; Jordan P. Todes; Alexandre Pohl; Tripti Bhattacharya; Bas van de Schootbrugge; Paul B. Wignall; Simona Todaro; et al. (Chemical Geology, 2025)

An Ordovician Assemblage of Cool Water‐Adapted Paleotropical Ostracods Suggests an Early Psychrosphere - Anna McGairy; Phong Duc Nguyen; Mark Williams; Christopher P. Stocker; Thomas H. P. Harvey; Toshifumi Komatsu; Thomas W. Wong Hearing; C. Giles Miller; Chloé M. Marcilly; Alexandre Pohl (Island Arc, 2025)
An ostracod assemblage from the Late Ordovician (Katian) Phu Ngu Formation of northern Vietnam, South China paleoplate, yields typical Baltic and Laurentian‐affinity genera together with some endemic forms. Detailed paleontological and sedimentary analysis of the Phu Ngu Formation suggests it was deposited in a deeper marine forearc setting, below storm wave base, but with (at least intermittently) oxygenated sea‐bottom conditions. Taphonomic assessment of the ostracod assemblage suggests it is in situ. The occurrence of globally widespread ostracod genera, including those from paleocontinents that were geographically remote from South China, is difficult to reconcile with the assumed limited dispersal capability of ostracods in shallow‐shelf settings—a characteristic that has often been used to refine Ordovician paleogeographical reconstructions. Here, we present the novel approach of using paleoclimate reconstructions to assess the environmental distributions of Paleozoic ostracod genera. We show that the deep‐marine depositional setting of our documented assemblage, together with general circulation model simulations of Ordovician ocean‐temperatures, suggests an early radiation of benthic ostracods into the deeper, colder, and thermally uniform ocean below the thermocline. The presence of a globally‐distributed psychrospheric (cool and deep marine) ostracod fauna would imply that our understanding of Ordovician ostracod dispersal is incomplete, and future paleobiogeographical studies should try to decouple the signal of shallow‐shelf benthic taxa, often endemic and probably limited by sea temperature, from those that are more cosmopolitan and tolerant of cooler, deeper waters.

Phenology Across Scales: An Intercontinental Analysis of Leaf‐Out Dates in Temperate Deciduous Tree Communities - Nicolas Delpierre; Suzon Garnier; Hugo Treuil‐Dussouet; Koen Hufkens; Jianhong Lin; Colin Beier; Michael Bell; Daniel Berveiller; Matthias Cuntz; Giulio Curioni; Kyla Dahlin; Sander O. Denham; et al. (Global Ecology and Biogeography, 2024)
Aim To quantify the intra‐community variability of leaf‐out (ICVLo) among dominant trees in temperate deciduous forests, assess its links with specific and phylogenetic diversity, identify its environmental drivers and deduce its ecological consequences with regard to radiation received and exposure to late frost. Location Eastern North America (ENA) and Europe (EUR). Time Period 2009–2022. Major Taxa Studied Temperate deciduous forest trees. Methods We developed an approach to quantify ICVLo through the analysis of RGB images taken from phenological cameras. We related ICVLo to species richness, phylogenetic diversity and environmental conditions. We quantified the intra‐community variability of the amount of radiation received and of exposure to late frost. Results Leaf‐out occurred over a longer time interval in ENA than in EUR. The sensitivity of leaf‐out to temperature was identical in both regions (−3.4 days per °C). The distributions of ICVLo were similar in EUR and ENA forests, despite the latter being more species‐rich and phylogenetically diverse. In both regions, cooler conditions and an earlier occurrence of leaf‐out resulted in higher ICVLo. ICVLo resulted in ca. 8% difference of radiation received from leaf‐out to September among individual trees. Forest communities in ENA had shorter safety margins as regards the exposure to late frosts, and were actually more frequently exposed to late frosts. Main Conclusions We conducted the first intercontinental analysis of the variability of leaf‐out at the scale of tree communities. North American and European forests showed similar ICVLo, in spite of their differences in terms of species richness and phylogenetic diversity, highlighting the relevance of environmental controls on ICVLo. We quantified two ecological implications of ICVLo (difference in terms of radiation received and exposure to late frost), which should be explored in the context of ongoing climate change, which affects trees differently according to their phenological niche.

Recurrent marine anoxia in the Paleo-Tethys linked to constriction of seaways during the Early Triassic - Yuyang Wu; Alexandre Pohl; Li Tian; Jacopo Dal Corso; Ying Cui; Daoliang Chu; Jinnan Tong; Huyue Song; Hanchen Song; Haijun Song (Earth and Planetary Science Letters, 2024)

The dynamic ocean redox evolution during the late Cambrian SPICE: Evidence from the I/Ca proxy - Ruliang He; Alexandre Pohl; Ashley Prow; Ganqing Jiang; Chin Chai Huan; Matthew R. Saltzman; Zunli Lu (Global and Planetary Change, 2024)

Marine carbonate factories: a global model of carbonate platform distribution - Julien Michel; Marie Laugié; Alexandre Pohl; Cyprien Lanteaume; Jean-Pierre Masse; Yannick Donnadieu; Jean Borgomano (International Journal of Earth Sciences, 2019)

Geomatic downscaling of temperatures in the Mont Blanc massif - Daniel Joly; Alexandre Berger; Jean‐François Buoncristiani; Olivier Champagne; Julien Pergaud; Yves Richard; Paul Soare; Benjamin Pohl (International Journal of Climatology, 2018)
This article presents a novel downscaling method based on a geomatic spatial model. This model is constructed on the basis of regressions between topographical (explanatory) variables (digitized here at 200 m resolution) and climatic factors observed at meteorological stations. These regressions are used to calibrate the model in the form of two parameters: the frequency with which explanatory variables are significant at the 95% level, and the mean of the regression coefficient associated with each variable. One of the objectives of the article is to test the relevance of the method and the application made of it in this study bears on daily observed minimum (tn) and maximum (tx) temperatures in the Mont Blanc massif between 1979 and 2014. Estimations show weak statistical biases and the temperature variation from day to day is well represented. The root mean square errors of daily temperatures are of the order of 2 °C for tn and tx alike. The validation shows (1) the value of applying spatial models to two atmospheric configurations (weather regimes and local rainfall conditions) and (2) the limitations of the method. Eventually, this method shall be applied to the downscaling of large‐scale atmospheric parameters provided by earth system models for projecting the temperature of the lower layers of the atmosphere over future decades.

The relationship between plant species richness and soil aggregate stability can depend on disturbance - Mandy Pohl; Frank Graf; Alexandre Buttler; Christian Rixen (Plant and Soil, 2012)

Amazonian Tree Mortality during the 1997 El Niño Drought - G. Bruce Williamson; William F. Laurance; Alexandre A. Oliveira; Patricia Delamônica; Claude Gascon; Thomas E. Lovejoy; Luciano Pohl (Conservation Biology, 2000)
In 1997, the Amazon Basin experienced an exceptionally severe El Niño drought. We assessed effects of this rare event on mortality rates of trees in intact rain forest based on data from permanent plots. Long‐term (5‐ to 13‐year) mortality rates averaged only 1.12% per year prior to the drought. During the drought year, annual mortality jumped to 1.91% but abruptly fell back to 1.23% in the year following El Niño. Trees dying during the drought did not differ significantly in size or species composition from those that died previously, and there was no detectable effect of soil texture on mortality rates. These results suggest that intact Amazonian rainforests are relatively resistant to severe El Niño events.